Waging war a new philosophical introduction - Clark, Ian (Oxford University Press, 2015)
What exactly is it we wage when we wage war? This is the crucial question addressed in this largely rewritten edition of the author's classic text. The book shows how recent developments in warfare, particularly related to new technologies and asymmetries, have disturbed traditional paradigms.